Come back, salmon : how a group of dedicated kids adopted Pigeon Creek and brought it back to life - Cone, Molly; Wheelwright, Sidnee (San Francisco : Sierra Club Books for Children, 1992)
Describes the efforts of the Jackson Elementary School in Everett, Washington, to clean up a nearby stream, stock it with salmon, and preserve it as an unpolluted place where the salmon could return to spawn.
Includes index.
Keywords: Jackson Elementary School (Everett, Wash.) -- Juvenile literature; Jackson Elementary School (Everett, Wash.); Fish habitat improvement -- Washington (State) -- Pigeon Creek -- Citizen participation -- Juvenile literature; Coho salmon -- Washington (State) -- Pigeon Creek -- Juvenile literature; Pacific salmon -- Juvenile literature; Fish habitat improvement; Salmon; Environmental protection